An Uncemented Spreading Stem for the Fixation in the Metaphyseal Femur: A Preliminary Report. (15th May 2016) - Burger, Daniel; Pumberger, Matthias; Fuchs, Bruno
Abstract : Surgical treatment to restore full range of motion and full weight bearing after extensive femoral bone resection in patients with primary or metastatic femoral tumours is individually challenging. Especially when the remaining distal or proximal bone is very short, a rigid fixation of an implant is difficult to achieve due to the reverse funnel shape of the metaphysis. Herein, we present a novel implant design using a spreading mechanism in the distal part of the prosthesis for rigid, uncemented fixation in the remaining femoral bone after extensive tumour resection of the femur. We present the outcome of 5 female patients who underwent implantation of this spreading stem after extensive proximal or distal femoral bone resection. There was no radiological or clinical loosening or implant-related revision surgery in our follow-up (mean 21.46 months, range 3.5–46 months). This uncemented spreading stem may therefore represent an alternative option for fixation of a prosthetic device in the remaining metaphyseal femur.